2022
DOI: 10.5935/1984-0063.20220045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antiepileptic drugs on sleep architecture parameters in adults

Abstract: Objectives Physiological and restorative sleep is fundamental for physical and mental well-being. Polysomnography parameters are objective methods to access sleep structure. Antiepileptic drugs (AEDs) are a group of drugs whose interference in the sleep structure is still not well known, especially in what concern the new ones. We did a systematic review of the literature to compare the effect of classic and newer AEDs on sleep architecture. Material and Methods A searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…In addition, cognitive function and QoL were not negatively impacted following perampanel monotherapy or first adjunctive therapy. These findings are supported by previous evidence that suggests perampanel can have a positive effect on sleep quality [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, cognitive function and QoL were not negatively impacted following perampanel monotherapy or first adjunctive therapy. These findings are supported by previous evidence that suggests perampanel can have a positive effect on sleep quality [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 89%
“…Cognitive function and QoL in patients with epilepsy can be negatively affected by poor sleep quality. The use of some ASMs can lead to disruptions in sleep quality, such as daytime sleepiness, which can worsen seizure control [ 30 ]. Here, we demonstrated that perampanel did not adversely affect sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepines, which were commonly used in our cohort, may also increase the risk of respiratory depression and oxygen desaturation nadir. 13 Conversely, other ASMs such as carbamazepine, phenobarbitone, valproate, clobazam, clonazepam, phenytoin, and levetiracetam decrease rapid eye movement (REM) sleep 14 ; this may underscore the severity of respiratory disturbances in this patient group, which is often exacerbated during REM sleep. Other antiseizure treatments such as vagus nerve stimulation can exacerbate respiratory depression.…”
Section: Discussionmentioning
confidence: 99%
“…Among these effects, sleep-dependent interictal epileptiform events particularly during non-REM sleep ( Urbain et al, 2011 ; Bjørnæs et al, 2013 ; Galer et al, 2015 ; Halász et al, 2019 ) and sleep-related seizures ( Malow, 2007 ) partly explain hampered sleep-related memory consolidation in people with epilepsy. Additionally, anti-seizure drugs impact brain activity, e.g., by increasing or decreasing power in specific frequency bands ( Höller et al, 2018 ; Höller and Nardone, 2021 ) and they can change sleep architecture by extending or shortening specific sleep stages ( Carvalho et al, 2022 ). Thus, it is plausible that anti-seizure drugs also impact sleep-related consolidation of memory, but the exact nature of this relationship is poorly understood.…”
Section: Introductionmentioning
confidence: 99%